EFEKTIVITAS PROGRAM KELOMPOK TANI PADI DI DESA WOLAANG KECAMATAN LANGOWAN TIMUR KABUPATEN MINAHASA - MOTULO, BRENDA; MANDEY, LUCIA; TULUNG, Max (JURNAL ADMINISTRASI PUBLIK, 2019)
Farmer groups are one form of community efforts to live better in the economic field. Thisresearch was carried out with the main objectives: to find out the extent of the effectiveness of the ricefarmer group program in Wolaang Village, East Langowan District, Minahasa Regency, to find out theobstacles in the process of implementing the rice farmer group program in Wolaang and to find out theefforts to overcome the obstacles encountered in the process of implementing the rice farmer groupprogram in Wolaang. The researcher used descriptive qualitative method, data was collected byinterviewing ten informants, observing, and using related documents. The research data is analyzedthrough SWOT analysis which is a strategic planning method used to evaluate strengths, weaknesses,opportunities, and threats in a project or business speculation. The four factors that form the SWOTacronym (strengths, weaknesses, opportunities, and threats). And in the results of the research programthe rice farmer groups in this village have not been effective because 1) have not succeeded in recruitingsmall farmers and communities who have not worked according to the program's main objectives. 2) thereare 10 registered rice farmer groups but only 4 are active due to lack of insight and activities carried out inthe program. 3) Not all members of the rice farmer group are satisfied with the program that has beenmade for a long time because of the lack of supervision and attention of the government so that the ricefarmers prefer to work personally. 4) Supporting facilities are inadequate; Lack of control when workingso that targets are sometimes inappropriate; The report on the use of funds is not very good; Processingland that is still traditional so it takes a long time; The use of funds has not been as needed; Less optimalaccommodation; Weak carrying capacity of citizens to work; Updates to equipment; Circumstances thathinder program mobility; Less than working. 5) the emergence of new farmer groups causes less funding from the government because of the increase in the number of farmer groups; Transfer of farmer groupmembers to new farmer groups; Competition fights for the sympathy of the government and newagricultural land with competitors; and new farmer groups often emerge with a more modern and strongstyle in terms of funding. The suggestions that I can give to Wolaang village farmer groups and theirgovernments are: 1) increasing supervision. 2) pay attention to funding management. 3) increase workmotivation 4) improve the quality and availability of supporting facilities and infrastructure. 5) increasinghealthy competition with beginner farmer groups.Keywords: Farmer Group, Effectiveness, Farmer Group Work Program.